On the Teaching of Islam at Luther Seminary - Swanson, Mark N. (Teaching theology and religion, 2005)
In a brief essay originally presented as part of a panel discussion with Christian and Muslim teachers of Islam in the university setting, the author describes the distinctive characteristics of the Islamic Studies Program at Luther Seminary (St. Paul, Minnesota). While the program allows Islamic studies “majors” to earn a degree (M.A. or M.Th.) or certificate in the field, it also aims to be accessible to students in all degree and non-degree programs of the seminary. The author names three sets of issues that result from the determination, at one and the same time, to be faithful Christian theologians and to honor Muslims and their traditions: the hermeneutical issues arising when Christians attempt to read Muslims’ sacred scripture; the challenges of developing a dialogical theology in relation to Islam; and questions about the character and practice of Christian witness in a world shared with Muslims, themselves called to da‘wah.